Study of Islam in Religious Moderation (Study of Moderate Islamic Thoughts in Indonesia) - Darul Qutni; Abdul Ghofur; Ismawati Hafied; Ahmad Muthohar; Zaim Elmubarok (Zien Journals, 2022)
The Islamic teachings refer to Al-Qur'an and al-Hadith. However, current phenomena show that there are many types of Islamic teaching implementations. Many Islamic groups sometimes have their characteristics in religious practices. The differences have become natural, sunatullah, and even a blessing. Quraish Shihab noted that "diversity in life is a necessity that Allah SWT wills. This includes differences and diversity of opinions in the scientific fields. There are even different human responses regarding the truth of the holy books (Quran), the interpretation of their contents, and the form of their practices" (Quraish Shihab, 2007: 52). Of the various kinds of diversity that Indonesia has, the religious one is the strongest in triggering radicalism in Indonesia. The existence of extremist groups that are increasingly expanding their wings is generated in by many factors like sensitivity to religious life, an influx of foreign extremist groups, and even political and government problems. Amid the hustle and bustle of this radicalism problem, there is a term called "religious moderation". The problem is whether those who practice the religion can respect each other, and are willing to have a dialogue to solve any issue. If it becomes a foothold in charity and religion, it is the meaning of the concept of "moderate Islam.” This research is a qualitative research using descriptive method. The reason for using qualitative research is because this research is related to data that needs to be analyzed descriptively and efforts to solve the research problem have three stages: (1) providing data, (2) analyzing data and (3) assessing the results of data analysis
Keywords: Religious Moderation and Islamic Thoughts; results; government